Exploratory Investigation of Intestinal Function and Bacterial Translocation After Focal Cerebral Ischemia in the Mouse - Oyama, Naoki; Winek, Katarzyna; Bäcker-Koduah, Priscilla; Zhang, Tian; Dames, Claudia; Werich, Martina; Kershaw, Olivia; Meisel, Christian; Meisel, Andreas; Dirnagl, Ulrich (Frontiers in Neurology, 2018)
Background and Purpose: The gut communicates with the brain bidirectionally via neural, humoral and immune pathways. All these pathways are affected by acute brain lesions, such as stroke. Brain-gut communication may therefore impact on the overall outcome after CNS-injury. Until now, contradictory reports on intestinal function and translocation of gut bacteria after experimental stroke have been published. Accordingly, we aimed to specifically investigate the effects of transient focal cerebral ischemia on intestinal permeability, gut associated lymphoid tissue and bacterial translocation in an exploratory study using a well-characterized murine stroke model. Methods: After 60 minutes of middle cerebral artery occlusion (MCAO) we assessed intestinal morphology (time points after surgery day 0, 3, 5, 14, 21) and tight junction protein expression (occludin and claudin-1 at day 1 and 3) in 12-week-old male C57Bl/6J mice. Lactulose/mannitol/sucralose test was performed to assess intestinal permeability 24 to 72 hours after surgery. To investigate the influence of cerebral ischemia on the local immune system of the gut, main immune cell populations in Peyer´s patches (PP) were quantified by flow cytometry. Finally, we evaluated bacterial translocation to extraintestinal organs 24 and 72 hours after MCAO by microbiological culture and fluorescence in situ hybridization targeting bacterial 16S rRNA. Results: Transient MCAO decreased claudin-1 expression in the ileum but not in the colon. Intestinal morphology (assessed by light microscopy) and permeability did not change measurably after MCAO. After MCAO, animals had significantly fewer B cells in PP compared to naïve mice. Conclusions: In a murine model of stroke which leads to large brain infarctions in the middle cerebral artery territory we did not find evidence for overt alterations neither in gut morphology, barrier proteins and permeability nor presence of intestinal bacterial translocation.